Tolerancing Mechanical Assemblies Using Computer Aided Design and Experimental Design - Shin, Garrick; Graves, Spencer; Bisgaard, Soren (My University, 1997)
Component tolerances for assembled products are often set with the help of the error transmission formula. However, this approach requires knowledge of the partial derivatives of the functional relationship between the component dimensions and the assembly quality characteristic. In many practical situations, those numbers are not easily obtained. In this article we will demonstrate a novel combined use of computer aided design (CAD) and design of experiments (DOX) to obtain partial derivatives of the functional relationship. With knowledge of these, we can use the error transmission formula to establish functional tolerances. The intent of the present article is to demonstrate, with some examples, an idea and a set of techniques that can be used to set functional tolerances for mechanical components and assemblies.